Lanthanum functionalized highly ordered mesoporous media: implications of arsenate removal - Jang, Min; Park, J.K.; Shin, E.W. (Elsevier, 2004)
A highly ordered mesoporous silica, SBA-15, was synthesized and various amounts of lanthanum oxide were incorporated into it. Several characterization techniques, such as X-ray diffraction (XRD), nitrogen gas isotherm, and Fourier transform infrared (FTIR) spectroscopy were used to investigate physicochemical properties of the media and to elucidate their arsenate adsorption behavior. The X-ray diffraction and N2 isotherm results showed that immoderate substitution of lanthanum in the silica network occurred at 80 lanthanum impregnation, even though the lanthanum was highly dispersed inside the mesopore structures of SBA-15 and lanthanum oxide particles did not form on the outside of the solid. As a result of FTIR, however, there was no structural collapse of the silica framework at 80 lanthanum impregnation since partial substitution of lanthanum precursors with silicon occurred; this may play an important role in structural stabilization, as shown by other studies. Although the arsenate adsorption densities increased with an increase in lanthanum impregnation up to 50 (the most efficient percentage of lanthanum impregnation), it. abruptly decreased at 80 due to the substitution of lanthanum with silicon, leading to an overall reduction in arsenate adsorption capacity. At the arsenate concentration of 0.667 mmolAs/l, the adsorption capacity of 50 lanthanum-impregnated SBA-15 by weight (designated as La50SBA-15) was 1.651 mmolAs/g (123.7 mgAs/g), which was approximately 10 and 14 times greater than La(III) impregnated alumina and La(III) impregnated silica gel, respectively. Â© 2004 Published by Elsevier Inc.